Knowledge diversity and coordination: The effect of intrafirm inventor task networks on absorption speed - Moreira, Solon; Markus, Arjan; Laursen, Keld (Strategic Management Journal, 2018)
[Research Summary: We combine the absorptive capacity and social network theory approaches to predict how intrafirm "whole" network characteristics affect the firm's speed of absorption of external knowledge to produce inventions. We start from the widely accepted view that distant, externally-developed knowledge is difficult to absorb into the focal firm's own knowledge production. We suggest that high levels of intrafirm inventor task network diversity and task network density are essential for a diversity of knowledge inputs and coordinated actions regarding knowledge transfer, which in turn, reduces problems related to the absorption of knowledge—especially in the case of knowledge that is distant from the focal firm. The results of an event history study of 113 pharmaceutical firms that engaged in technology in-licensing from 1986 to 2003 provide general support for our hypotheses. Managerial Summary: Firms keen to keep up with an uncertain and ever-changing industry environment, can benefit from the speedy introduction of inventions. We examine how firms absorb licensed-in technologies to nurture the rapid development of own related inventions. We show that a firm's absorption speed depends on the characteristics of the internal collaboration networks among the firm's inventor employees. More specifically, technologically diverse and well-connected inventor networks improve the firm's ability to absorb external technologies quickly. This applies especially to externally acquired technologies that are unfamiliar to the firm. Depending on the distance of the acquired technology from the focal firm combined with speed-inducing inventor network characteristics, our estimates suggest that firms can reduce the time needed for absorption by several months.]